2018
DOI: 10.1177/2043808718779431
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the relationship between rigidity/flexibility and transdiagnostic cognitive and behavioral processes that maintain psychopathology

Abstract: An ever-growing number of transdiagnostic processes that maintain psychopathology across disorders have been identified. However, such processes are not consistently associated with psychological distress and symptoms. An understanding of what makes such processes pathological is required. One possibility is that individual differences in rigidity in the implementation of these processes determine the degree of psychopathology. The aim of this article is to examine the relationship between rigidity/flexibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 206 publications
9
84
0
2
Order By: Relevance
“…Both show a strong relationship to rigid perfectionism, which is increasingly identified as a transdiagnostic process (Egan, Wade, & Shafran, 2011), as well as obsessive-compulsiveness, including anankastia/obsessive-compulsive personality disorder (OCPD). These are associated with a strong need for control (ICD-11 -World Health Organization, 2019; DSM-5 -American Psychiatric Association, 2013), as well as related to rigidity/flexibility, consistently with the assumption that inflexibility in the transdiagnostic processes is essential in making them problematic and pathological (Morris & Mansell, 2018). Similar family factors have been suggested as crucial for both disorders (e.g., enmeshment and criticism), and it was suggested that they generally might represent a way of coping with problems of identity and personal control (Polivy & Herman, 2002), specifically as a way to compensate for low self-esteem (see Andreassen, 2014;Atroszko, Demetrovics, & Griffiths, 2019;.…”
Section: Discussionmentioning
confidence: 99%
“…Both show a strong relationship to rigid perfectionism, which is increasingly identified as a transdiagnostic process (Egan, Wade, & Shafran, 2011), as well as obsessive-compulsiveness, including anankastia/obsessive-compulsive personality disorder (OCPD). These are associated with a strong need for control (ICD-11 -World Health Organization, 2019; DSM-5 -American Psychiatric Association, 2013), as well as related to rigidity/flexibility, consistently with the assumption that inflexibility in the transdiagnostic processes is essential in making them problematic and pathological (Morris & Mansell, 2018). Similar family factors have been suggested as crucial for both disorders (e.g., enmeshment and criticism), and it was suggested that they generally might represent a way of coping with problems of identity and personal control (Polivy & Herman, 2002), specifically as a way to compensate for low self-esteem (see Andreassen, 2014;Atroszko, Demetrovics, & Griffiths, 2019;.…”
Section: Discussionmentioning
confidence: 99%
“…The theory recognizes that since complete influence over events is rarely possible, the way to sustain adequate control, and thus avoid conflict and distress, is to recognize and adjust or abandon goals that cannot be achieved ( Brandtstädter, 2009 ; Morris, Mansell, & McEvoy, 2016 ; Powers, 1973 ). This change happens through a trial and error process termed reorganization ( Powers, 1973 ).…”
Section: Overall Conceptualizationmentioning
confidence: 99%
“…Training programmes need to provide techniques for responding to daily challenges that encourage the resolution of internal conflicts between higher-level goals, because this will increase the scope for control and thus promote resilience ( Alsawy et al., 2014 ; Dias et al., 2015 ; Harmell et al., 2011 ; Morris et al., 2016 ). As noted above, reorganizing and resolving higher-level conflicts is also likely to improve communication, because it reduces the likelihood of external conflict.…”
Section: Towards Supportive Interventions In Carer Training: the Commmentioning
confidence: 99%
See 1 more Smart Citation
“…The two key elements here are a broad awareness of higher level goals (including goals that could potentially conflict) in conjunction with a mobility of awareness, so that an individual does not “get stuck” at higher level abstract goals but is able to implement higher level reorganization using lower level goals (Morris, Mansell, & McEvoy, ). Behaviourally, this might be demonstrated by the ability to disengage from patterns of responding that are no longer helpful in meeting an individual's important goals (Morris & Mansell, in press). Varied strands of evidence indicate that mindfulness can enable a broad and mobile awareness that allows access to conflicted goals and distressing experiences.…”
Section: Introductionmentioning
confidence: 99%